The Functional Anatomy of Psychomotor Disturbances in Major Depressive Disorder - Liberg, Benny; Rahm, Christoffer (Frontiers in Psychiatry, 2015)
Psychomotor disturbances (PMD) are a classic feature of depressive disorder that provide rich clinical information. The aim our narrative review was to characterize the functional anatomy of PMD by summarizing findings from neuroimaging studies. We found evidence across several neuroimaging modalities that suggest involvement of fronto-striatal neurocircuitry, and monoaminergic pathways and metabolism. We suggest that PMD in major depressive disorder emerge from an alteration of limbic signals, which influence emotion, volition, higher-order cognitive functions, and movement.